2017
DOI: 10.1016/j.foodres.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mouthfeel in model wines: Sensory-to-instrumental approaches

Abstract: Wine creates a group of oral-tactile stimulations not related to taste or aroma, such as astringency or fullness; better known as mouthfeel. During wine consumption, mouthfeel is affected by ethanol content, phenolic compounds and their interactions with the oral components. Mouthfeel arises through changes in the salivary film when wine is consumed. In order to understand the role of each wine component, eight different model wines with/without ethanol (8%), glycerol (10g/L) and commercial tannins (1g/L) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…The O 2 measurements were carried out through up to four saturation cycles for about 90 days (36 trials, including model solution and red wine). The duration of the monitoring is compatible with the production of young red wines [35] and the dosage of tannin added to model wine solution is consistent with the literature [36,37]. Figure 1 shows the oxygen consumption over time in the model solution for three consecutive saturations, demonstrating the dose-response effect of oenological tannins.…”
Section: Resultssupporting
confidence: 83%
“…The O 2 measurements were carried out through up to four saturation cycles for about 90 days (36 trials, including model solution and red wine). The duration of the monitoring is compatible with the production of young red wines [35] and the dosage of tannin added to model wine solution is consistent with the literature [36,37]. Figure 1 shows the oxygen consumption over time in the model solution for three consecutive saturations, demonstrating the dose-response effect of oenological tannins.…”
Section: Resultssupporting
confidence: 83%
“…Currently oral tribology is emerging as a promising tool to quantify friction and lubrication of food‐saliva mixtures in the oral mucosa using in vitro polymeric set up (Laguna et al, ; Laguna, Farrell, Bryant, Morina, & Sarkar, ; Laguna & Sarkar, ). Studies involving xerostomia patients have reported reduced sulfation of salivary mucins (both MUC1 and MUC2), which may affect the lubricating property of saliva (Chaudhury et al, ).…”
Section: Changes In Quantity and Quality Of Bulk Saliva On Agingmentioning
confidence: 99%
“…In the process of production and storage of red wine, some edible compounds are generally added such as Na 2-SO 3 for removing oxygen (Isaac et al, 2006), tartaric acid for acidizing red wine (Gomez et al, 1993), tannin as a stabilizer (Laguna et al, 2017) and glucose as exogenous substrate in fermentation progression (18 g/L of sugar is fermented into 1% alcohol). It is reported that, besides removing oxygen, Na 2 SO 3 could be used as an essential preservative to prevent microbial spoilage and extend the shelf life (Spricigo et al, 2010) as well as inhibit the browning reactions and improve the overall quality of the red wine (Guan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%